Anatomia floral de espécies de Eriocaulaceae e de Cephalostemon riedelianus Koern. (Rapateaceae) - Rosa, Michele Marcelino [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
No presente trabalho foi estudada a anatomia floral de Actinocephalus polyanthus, Leiothrix fluitans, Paepalanthus chlorocephalus, P. flaccidus e Rondonanthus roraimae, pertencentes à Eriocaulaceae, e de Cephalostemon riedelianus, pertencente à Rapateaceae, procurando contribuir com o maior conhecimento de representantes de Poales. Nas Eriocaulaceae, as flores estaminadas e pistiladas são trímeras na maioria das espécies e dímeras em P. flaccidus. Nas flores estaminadas de todas as espécies, o androceu é isostêmone, e em A. polyanthus, L. fluitans, P. chlorocephalus e P. flaccidus são encontrados estaminódios escamiformes microscópicos adnatos à base dos filetes. Nas flores pistiladas, os estaminódios são reduzidos, adnatos à base das pétalas, e em R. roraimae são lineares, alongados e vascularizados. As flores pistiladas de todas as espécies de Eriocaulaceae apresentam estiletes sólidos, desprovidos de vascularização e intercalados por apêndices nectaríferos que são vascularizados pelos feixes dorsais dos carpelos. Os apêndices nectaríferos são homólogos aos estiletes. A presença de androceu isostêmone pode ser considerada como um caráter derivado em Eriocaulaceae a partir da redução das peças florais de um provável ancestral com androceu diplostêmone. A ausência de estaminódios nas flores estaminadas de R. roraimae e a presença de estaminódios vascularizados nas suas flores pistiladas, indicam sua provável posição basal em relação aos demais representantes da subfamília Paepalanthoideae. A presença de apêndices nectaríferos pode ser considerada tanto um caráter derivado como um caráter ancestral em Eriocaulaceae a partir da modificação do gineceu do provável ancestral. Em relação à Rapateaceae, as flores de C. riedelianus são perfeitas, trímeras e apresentam androceu diplostêmone...

In order to contribute to a better knowledge of Poales specimens, the present work studied the floral anatomy of Actinocephalus polyanthus, Leiothrix fluitans, Paepalanthus chlorocephalus, P. flaccidus and Rondonanthus roraimae, belonging to the Eriocaulaceae, and of Cephalostemon riedelianus, belonging to the Rapateaceae. All the staminate and pistillate flowers of these Eriocaulaceae are trimerous except those of P. flaccidus, which are dimerous. All the staminate flowers of these species have an isostemonous androecium and A. polyanthus, L. fluitans, P. chlorocephalus and P. flaccidus present microscopic, scalelike staminodes adnate to the filament base. The staminodes of the pistillate flowers are reduced and adnate to the petal basis, except those of R. roraimae that are linear, elongated and vascularized. The pistillate flowers of all these Eriocaulaceae species present solid styles, devoid of vascularization and interspersed with nectariferous appendages, which are vascularized by the dorsal bundles of the carpels. The nectariferous appendages are homologous to the styles. The presence of an isostemonous androecium can be considered in Eriocaulaceae as a derived feature from the reduction of the floral parts from a probable ancestor with a diplostemonous androecium. The absence of staminodes in the staminate flowers of R. roraimae and the presence of vascularized staminodes in its pistillate flowers indicate its probable basal position in relation to other specimens of the subfamily Paepalanthoideae. In Eriocaulaceae, the presence of nectariferous appendages could be considered either as an ancestral feature or as a derived one from the modification of the gynoecium of a probable ancestor. With regard to the Rapateaceae, the flowers of C. riedelianus are perfect, trimerous and present a diplostemonous androecium... (Complete abstract, click electronic address below)
Keywords: Anatomia vegetal; Monocotiledôneas; Flores